2005
DOI: 10.1016/j.jemermed.2004.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of patients with and without SARS WHO fulfilled the WHO SARS case definition

Abstract: To differentiate severe acute respiratory syndrome (SARS) from non-SARS illness, we retrospectively compared 53 patients with probable SARS and 31 patients with non-SARS who were admitted to Mackay Memorial Hospital from April 27 to June 16, 2003. Fever (> 38 degrees C) was the earliest symptom (50/53 SARS vs. 5/31 non-SARS, p < 0.0001), preceding cough by a mean of 4.5 days. The initial chest X-ray study was normal in 22/53 SARS cases versus 5/31 non-SARS cases. SARS patients with an initially normal chest X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Among 61 included studies on 57,798 subjects that reported cardiovascular comorbidities and outcomes, three were systematic reviews and meta-analyses, 35 were cohort studies (six were prospective and 28 were retrospective), three case-control studies, 17 case series, two case reports and one genetic network-based analysis (Supplementary Material Table 4). 1 , 23 , 48 , 49 , 52 , 57 , 60 , 63 , 71 –73, 75 , 79 – 83 , 85 , 87 , 89 , 92 132 In general, these studies were of fair to good quality.…”
Section: Resultsmentioning
confidence: 97%
“…Among 61 included studies on 57,798 subjects that reported cardiovascular comorbidities and outcomes, three were systematic reviews and meta-analyses, 35 were cohort studies (six were prospective and 28 were retrospective), three case-control studies, 17 case series, two case reports and one genetic network-based analysis (Supplementary Material Table 4). 1 , 23 , 48 , 49 , 52 , 57 , 60 , 63 , 71 –73, 75 , 79 – 83 , 85 , 87 , 89 , 92 132 In general, these studies were of fair to good quality.…”
Section: Resultsmentioning
confidence: 97%
“…Second, the lack of sufficient medical information on SARS meant that, although there was a rapid flow of information, often this was not robust scientific information. Rather, much of the information presented during the outbreak was based on opinion, guesswork and preliminary results (Chang et al, 2005;Drazen, 2003).…”
Section: Risk Perception and Communicationmentioning
confidence: 99%
“…A corresponding cost saving at an of 2.5 or greater can be achieved with $120 000 (95% CI: -330 000–520 000) to $740 000 (95% CI: 120 000 – 1 400 000) saved. Of note, if the proportion of positive cases is taken to be 8.0%, which represents the upper bound of SARS patient identification during the testing period for the 2003 epidemic, ( Rainer et al, 2007 , Chowell et al, 2015 , Chan et al, 2004 , Assiri et al, 2013 , Mohd et al, 2016 , Chang et al, 2005 ) the total cost of testing for negative patients is $1.9 million at this PIR.…”
Section: Resultsmentioning
confidence: 99%
“…For the main analysis, we ran 50 simulations with a set of parameters taken from literature; a rate of infection ( ) of 2.5 and incubation period (IP) of 4 days, ( Wu et al, 2020b ) and PIR rate 8.0% which is based on the upper bound for case identification in the SARS epidemic in 2003 ( Rainer et al, 2007 , Chowell et al, 2015 , Chan et al, 2004 , Assiri et al, 2013 , Mohd et al, 2016 , Chang et al, 2005 ). The full analysis was run for different parameter distributions ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation